Special Autonomy of Papua: A Review from the Perspective of the Unitary State of the Republic of Indonesia - Bauw, Lily (Faculty of Law Cenderawasih University, 2016)
The authority of governance in Papua Province through Act No. 21 of 2001 is very large, as stipulated in Article 4 paragraph (1), which covering all fields of government, except with regard to foreign affairs, defense and security, monetary and fiscal, religion, and justice, and except with regard to a particular field. In addition to the authority, the authority of Papua Province added with partial authority of the Government called a special authority as provided in paragraph (2) is the authority in the field of foreign policy, defense and security, monetary and fiscal, justice and religion. This authority, causing some people argues that leads to form a federal state and also may lead to the disintegration of nation. The assessment object with regard to the substance of Act No. 21 of 2001 that opposed to the concept of a unitary state, and designing a special autonomy of Papua in accordance with the principles of the Republic of Indonesia, by using juridical-normative. The result indicates that the special autonomy through Act No. 21 of 2001 does not conflict with the concept of a unitary state; it strengthens Papuan into the Unitary State of the Republic of Indonesia. Design of special autonomy in accordance with the principles of the Unitary State of the Republic of Indonesia that gives special powers to the province of Papua in the form of delegation of authority is clear and explicit to the Province of Papua through the implementation of devolution theory and delegation of authority from the provincial to the district/cities through the implementation of real household teachings.